Efektivitas Penggunaan Aplikasi Edukatif Interaktif YouTube Kids terhadap Kemampuan Literasi Dini Anak - Toyyibatut Thowilah (Zuriah Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the effectiveness of using the YouTube Kids interactive educational application in improving literacy skills for early childhood. Using a qualitative approach with a library research method, this study analyses various literatures, scientific journals and articles relevant to the topic. The results show that YouTube Kids, as a platform that presents audiovisual content with a child-friendly approach, can provide stimulus for the development of early literacy skills, such as letter recognition, vocabulary, and listening skills. However, its effectiveness is strongly influenced by parental supervision and appropriate content selection. This study recommends that educators and parents utilise YouTube Kids as a complementary rather than primary learning medium